2011
DOI: 10.1097/1939-4551-4-s3-s28
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in the Management of Chronic Urticaria

Abstract: The term "chronic idiopathic urticaria" denotes a spectrum of conditions with different poorly understood pathogenetic mechanisms in which the release of histamine plays a role. Nonsedating second-generation H1 antihistamines are postulated to be the first line of treatment of chronic idiopathic urticaria by national and international guidelines, but as control is not always achievable with the usually recommended doses, first-generation sedating antihistamines like hydroxyzine and diphenhydramine at high dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…Medications with alpha-adrenergic antagonistic properties, including trazodone and other antipsychotics, have been noted to carry an increased risk of inducing ischemic priapism [3,4]. While hydroxyzine is primarily an antihistaminergic agent, it has been noted to have alpha-adrenergic antagonistic properties due to a lack of receptor selectivity [5]. This lack of selectivity may be exacerbated at higher doses.…”
Section: Discussionmentioning
confidence: 99%
“…Medications with alpha-adrenergic antagonistic properties, including trazodone and other antipsychotics, have been noted to carry an increased risk of inducing ischemic priapism [3,4]. While hydroxyzine is primarily an antihistaminergic agent, it has been noted to have alpha-adrenergic antagonistic properties due to a lack of receptor selectivity [5]. This lack of selectivity may be exacerbated at higher doses.…”
Section: Discussionmentioning
confidence: 99%
“…El 35-50% de los pacientes tienen un mecanismo autoinmune, con autoanticuerpos frente a la cadena α del receptor de alta afinidad de IgE o contra la propia IgE (1,12) . Pacientes con UCI exhiben en promedio niveles de IgE total más altos en comparación con los controles sanos (13,14) .…”
Section: Fisiopatologíaunclassified
“…In the pre-omalizumab period, antihistamines (AHs) were the only US Food and Drug Administration (FDA)approved drug class for the treatment of CSU. The major challenge during that period was the treatment of patients not responding to AHs [5]. A meta-analysis showed that the rates of response to AHs at standard doses and updosing of AHs were 38.6% and 63.2%, respectively [6].…”
Section: Introductıonmentioning
confidence: 99%